(untitled) (SAARC Journal of Agriculture, 2025)
Malnutrition remains a significant public health concern in Bangladesh, with vitamin A deficiency posing a major public health issue. Orange-fleshed sweet potato (OFSP) is a nutrient-dense crop rich in provitamin A and other essential micronutrients and minerals, offering strong potential to combat this issue. However, its short shelf-life limits year-round availability and market access. This study, conducted in Gaibandha, Bangladesh during the 2020–2021 season, aimed to evaluate low-cost storage methods for extending shelf-life, reducing postharvest losses, and improving the marketability of sweet potato roots. Four storage methods—zero-energy cool chamber (T1), pit storage (T2), clamp storage (T3), and sand storage (T4) were tested using five sweet potato varieties: BARI SP 4 (V1), BARI SP 8 (V2), BARI SP 12 (V3), BARI SP 15 (V4), and a local variety (V5). The findings revealed that the zero-energy cool chamber (T1) and clamp storage (T3) were the most effective, particularly for BARI SP 12 (V3) and BARI SP 4 (V1), maintaining root quality with minimal losses, enhancing marketability and extending shelf-life up to three months. SAARC J. Agric., 23(1): 196-211 (2025)